Engaging Millennials: Role of Quality of Work Life, Psychological Safety, Psychological Capital, and Inclusive Leadership (A Study of 3-5 star Hotel Employees in Yogyakarta City) - Singarimbun, Abigael Sribuena; Suharti, Lieli (Universitas Mercu Buana, 2024)
Objectives: The millennial generation dominates the workforce in Indonesia, earning the title of